Self-management from an Islamic perspective - Alamri, Maha Mari; Alothman, ASHWAG IBRAHIM (Journal of Educational and Psychological Sciences, 2021)
The aim of the research is to read the concept and principles of self-management in an Islamic reading by identifying the concept of self-management from an Islamic perspective, the requirements for applying self-management, and evidence for self-management in Islam. The research used the descriptive documentary approach that relied on content analysis that provides an objective and structured description of the phenomenon studied. By relying on documents and books, by reviewing the concept of self-management and rooting it, presenting the most prominent influences in its application, then extrapolating the evidence that supports its principles on which modern thought was founded, and the research reached a number of results, most notably: the difference in the concept of the human self in Western thought among theorists throughout the ages While Islamic thought considers that the human self is honored and preferred by its creation, which is a point where the body meets the soul and the soul, and all that develops and directs these three aspects are considered self-management, so it is an integrative view that includes the material, emotional and skillful aspects. In light of these results, the research recommended several recommendations, including: the importance of accompanying the intention in every work that a person performs, and the organization of time, time is an essential element in effective management that needs vigilance for its assignments, that vigilance in which the self will achieve its goal, and to direct oneself towards his goal directly And to benefit from his talents that God has bestowed upon him in achieving the faculties that will help him in achieving this goal.
Keywords: Self- management; Islamic management; Islamic perspective